Teaching principles of inference with ANOVA. (24th July 2015) - Tarlow, Kevin R.
Summary: Analysis of variance (ANOVA) is a test of mean differences, but the reference to variances in the name is often overlooked. Classroom activities are presented to illustrate how ANOVA works with emphasis on how to think critically about inferential reasoning.